The Impact of Chronic Pain on Epilepsy: A Systematic Review - Yaffie Noor Rochim; Raras Windaswara; Kuswanto; Frida puspitasari; Yaffie Mohammad Rizaq (International Medical Journal Corp. Ltd, 2025)
Introduction: Epilepsy and chronic pain represent two of the most burdensome neurological conditions globally, each contributing significantly to disability and reduced quality of life. Emerging evidence suggests a clinical and pathophysiological overlap that is far greater than coincidental, pointing toward a synergistic negative impact when they co-occur. This systematic review aims to comprehensively evaluate the multifaceted impact of chronic pain on the clinical course, psychosocial well-being, and overall burden of epilepsy. Methods: A systematic search of PubMed, Scopus, and the Cochrane Library was conducted to identify relevant literature, including systematic reviews, meta-analyses, randomized controlled trials, and observational cohort studies. Search terms encompassed epilepsy, seizure disorders, chronic pain, neuropathic pain, migraine, and fibromyalgia. Studies were selected based on predefined eligibility criteria, and data were extracted and synthesized across key outcome domains, including epidemiology, pathophysiology, seizure control, quality of life, neuropsychiatric status, cognitive function, and socioeconomic burden. Results: The epidemiological data reveal a stark disparity: 40.2% of adults with active epilepsy report chronic pain, a rate double that of the general population (20.0%). This comorbidity is associated with adverse clinical outcomes, including the potential for increased seizure frequency, mediated by pain-induced chronic stress. The impact on patient well-being is profound, with comorbid pain compounding the already significant reduction in health-related quality of life (HRQoL) seen in epilepsy. The neuropsychiatric burden is dramatically amplified; notably, the presence of chronic pain is associated with a nearly four-fold increased risk of suicidal ideation in individuals with epilepsy (OR=3.86). This dyad also exacerbates cognitive deficits, sleep disturbances, and challenges in treatment adherence due to polypharmacy and increased side-effect burden. Consequently, the socioeconomic costs, both direct and indirect, are substantially magnified. Discussion: The findings underscore a complex, bidirectional relationship between chronic pain and epilepsy, likely driven by shared neurobiological mechanisms including neuronal hyperexcitability, central sensitization, and dysfunction of inhibitory GABAergic pathways. The therapeutic overlap of certain antiepileptic drugs further supports this mechanistic link. The clinical implications are significant, highlighting the inadequacy of treating epilepsy in isolation when chronic pain is present. The synergistic negative effects on mental health, QoL, and even suicide risk necessitate a paradigm shift in clinical practice. Conclusion: Chronic pain is not merely a passive comorbidity but a critical, disease-modifying factor that actively worsens the clinical trajectory and overall burden of epilepsy. Its presence undermines treatment efficacy and dramatically increases patient suffering and mortality risk. These findings advocate for the universal screening of pain and associated psychiatric conditions in epilepsy care and the implementation of integrated, multidisciplinary management strategies to improve patient outcomes.